The Grief and Loss Influence on Personality Changes in the Children's Book "The Heart and The Bottle" by Oliver Jeffers - Maharani, Kharien Puspa; Sutrisno, Djoko (JELLE, 2025)
The Heart and The Bottle is a children's book that tells the story of a girl who has a lot of curiosity. She often spends her time exploring the world with her father. However, she suddenly has to face the grief of her father's death. The objective of this research is to find out how grief affects the main character's personality change. This research will be studied by using the descriptive qualitative method. The main data source is from the narrative in the book The Heart and The Bottle. Based on the findings, it is known that the personality change of the main character occurs gradually. At first, she began to lose interest in what she liked all this time due to the feelings of grief that still lingered over her. At the end of the story, the girl finally begins to open herself up and return to her true self again.